Pengaruh Good Corporate Governance Terhadap Kualitas Pelaporan Keuangan Di Badan Usaha Milik Negara - Arlis Dewi Kuraesin; Winwin Yadiati (UNIVED Press, 2021)
This article aims to determine the effect of Good Corporate Governance on the quality of financial reporting. The method used in this research is descriptive and verification method (verificative research). Based on the results of hypothesis testing using eviews 9. there is a relationship between good corporate governance and the quality of financial reporting which is reflected in the value of 0.196722. Furthermore, good corporate governance has an impact on the quality of financial reporting which is reflected in the value of 0.8104. The results of this test prove that good corporate governance affects the quality of financial reporting.